ECOLOGICAL OBSERVATIONS ON INQUILINISM IN SOME CRUSTACEANS - RIOJA, ENRIQUE (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1950)
Known types of crustacean inquilinism are briefly discussed, and 5 types of adaptation are pointed out loss of pigment, reduction and depigmentation of the eye, modification of organs (especially locomotor) as attachment devices, development of a cylindri
REV SOC MEX HIST NAT
Keywords: ECOLOGICAL OBSERVATIONS, INQUILINISM, CRUSTACEANS; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA)